The Canada-US border in the 21st century trade, immigration and security in the age of Trump - Sutcliffe, John B.; Anderson, William P. 1954- (Routledge advances in regional economics, science and policy, 2019)
Borders are critical to the development and survival of modern states, offer security against external threats, and mark public policy and identity difference. At the same time, borders, and borderlands, are places where people, ideas, and economic goods meet and intermingle. The United States-Canada border demonstrates all of the characteristics of modern borders, and epitomises the debates that surround them. This book examines the development of the US-Canada border, provides a detailed analysis of its current operation, and concludes with an evaluation of the border's future. The central objective is to examine how the border functions in practice, presenting a series of case studies on its operation. This book will be of interest to scholars of North American integration and border studies, and to policy practitioners, who will be particularly interested in the case studies and what they say about the impact of border reform